Consumers' Purchase Intentions of Bi-national Products: Effects of Country-of-Brand, Country-of-Manufacture, and Trusting Beliefs. Issue 1 (1st January 2020) - Coffey, Shannon; Kabadayi, Sertan
Abstract: The prevalence of bi-national products necessitates decomposing of COO into its dimensions—country-of-brand (COB) and country-of-manufacture (COM)—to enable a fuller understanding of how COO affects consumer perceptions and intentions. This study examines how consumers' trusting beliefs about a brand moderate the negative COB/COM image and purchase intention relationship. More specifically, this article hypothesizes that three trusting beliefs weaken the effects of negative COB/COM image on consumers' purchase intention. Data for this study were collected from 405 participants using an online survey tool. A hierarchical moderated regression method was used to test the hypotheses. The results suggest that consumers' trusting beliefs have a significant moderating effect on COM/COB and purchase intention relationships. More precisely, benevolence and integrity beliefs about a brand were found to weaken the negative COB image and purchase intention relationship, while benevolence and ability beliefs lessen the effect of negative COM image on purchase intention.